OSA: A VANET application focused in energy efficiency (2014)
With the growth in the number of vehicles moving through the streets, high vehicular flow has become a mobility and public health problem for governmental institutions and people since time of travel, gasoline consumption, and greenhouse gas [GHG] emissions have suffered an important increase. Hereby, policies and actions are required to reduce the impact of this increase. In this context, we have developed an application for the simulation of Vehicular Ad hoc Networks [VANET] using two software applications: SUMO and OMNeT++. The application we developed optimizes fuel usage and reduces GHG emissions; showing that vehicles following a preset speed (previously studied), gasoline consumption and GHG emissions present a considerable decrease compared to vehicles not running at that speed. © 2014 IEEE.